Ciri-ciri pendidikan dan sosial pendudukan = education and social characteristics of the population (Banci penduduk dan perumahan Malaysia 2000, 2002)
The 2000 Population and Housing Census of Malaysia was the fourth decennial census to be conducted in Malaysia since the formation of Malaysia in 1963, the previous censuses being conducted in 1970, 1980 and 1991. The 2000 Census provides a wealth of information on the number of persons and households together with a wide range of their demographic characteristics. In addition, it also yields information on the number and type of living quarters as well as the availability of basic amenities.